THE IMPACT OF WORK CONFLICT, WORK ENVIRONMENT, AND SELF-AWARENESS ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT THE EMPLOYEES OF PROF. DR. CHAIRUDDIN PANUSUNAN LUBIS EDUCATIONAL HOSPITAL - Sartika Ningsih; Ritha F. Dalimunthe; Parapat Gultom (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Hospitals are considered as one of the organizations or health facilities that have an important role in improving the degree of public health. In an effort to provide comprehensive health services, an evaluation of the performance and satisfaction of hospital employees is needed. This study aims to find out and analyze the influence of work conflicts, work environment, and self-awareness on employee performance through job satisfaction of employees of Prof. Dr. Chairuddin Panusunan Lubis Teaching Hospital. This research is an associative research and the type of data used is quantitative data. The population in this study is an employee of the Prof. Dr. Chairuddin Panusunan Lubis Teaching Hospital. The number of samples in this study is 120 respondents. The data analysis used is structural equation modeling. The results of this study show that work conflicts directly have a negative and significant effect on job satisfaction and employee performance. Meanwhile, the work environment and self-awareness directly have a positive and significant effect on the work and performance of employees. Indirectly, work conflicts have a negative and significant effect on employee performance through job satisfaction. Meanwhile, the work environment and self-awareness indirectly have a positive and significant effect on employee performance through job satisfaction.